2014
DOI: 10.1038/ncomms5819
|View full text |Cite
|
Sign up to set email alerts
|

eEF2 and Ras-GAP SH3 domain-binding protein (G3BP1) modulate stress granule assembly during HIV-1 infection

Abstract: Stress granules (SG) are translationally silent sites of RNA triage induced by environmental stresses including viral infection. Here we show that HIV-1 Gag blocks SG assembly irrespective of eIF2α-phosphorylation and even when SG assembly is forced by overexpression of Ras-GAP SH3 domain-binding protein (G3BP1) or TIAR. The overexposed loops in the N-terminal Capsid domain of Gag and host eukaryotic elongation factor 2 (eEF2) are found to be critical for the SG blockade via interaction. Moreover, Cyclophilin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 69 publications
2
91
0
Order By: Relevance
“…The N-terminal Capsid domain of Gag (precursor viral polyprotein, processed into different viral proteins during maturation) interacts with eukaryotic elongation factor 2 (eEF2) to block SGs formation. To dismantle the already formed SGs, Gag recruits G3BP1 out the SGs (by displacing eEF2 with G3BP1) [116]. Infection with Rubella virus has also been shown to change the localization of host G3BPs, indicating that G3BPs may play an important role during infection by Rubella [117].…”
Section: Viral Targeting Of G3bps By Protein Interactionsmentioning
confidence: 99%
“…The N-terminal Capsid domain of Gag (precursor viral polyprotein, processed into different viral proteins during maturation) interacts with eukaryotic elongation factor 2 (eEF2) to block SGs formation. To dismantle the already formed SGs, Gag recruits G3BP1 out the SGs (by displacing eEF2 with G3BP1) [116]. Infection with Rubella virus has also been shown to change the localization of host G3BPs, indicating that G3BPs may play an important role during infection by Rubella [117].…”
Section: Viral Targeting Of G3bps By Protein Interactionsmentioning
confidence: 99%
“…chemical inhibitor of translation elongation and a well-characterized bona fide inhibitor of SG formation [20,32,50,51]. Given that the doses of CHX previously used to prevent SG formation (~100 lg/ml) also affect general translation to levels that are similar to AS treatment ( Fig 2B) [32,49,[51][52][53], we first determined the minimum dose of CHX that could prevent SG assembly without affecting the levels of newly synthesized proteins. We observed that 0.5 lg/ml of CHX for 30 min was sufficient to prevent both the formation of SGs ( Fig 4A) and the AS-mediated impairment of senescence in human fibroblasts ( Fig 4B and Appendix Fig S6).…”
Section: Sg Formation In the Proliferative Stage Prevents Cell Commitmentioning
confidence: 99%
“…Because HIV-1 Gag was recently reported to inhibit SG formation 33,34 , we also tested the effects of treating HeLa.YFP-A3G or HeLa.YFP-TIA1 biosensor cells with Ars at 31 hpi when NL4-3 Gag expression in HeLa cells is relatively high ( e.g. , see 31 ).…”
Section: Resultsmentioning
confidence: 99%